ChemInform Abstract: 3‐Naphthylindole Construction by Rhodium(II)‐Catalyzed Regioselective Direct Arylation of Indoles with 1‐Diazonaphthalen‐2‐(1H)‐ones. Issue 5 (January 2016) - Baral, Ek Raj; Lee, Yong Rok; Kim, Sung Hong
Abstract: The Rh‐catalyzed arylation of indoles (I) with 1‐diazonaphthalenones (II) affords a series of 3‐naphthylindoles (III) in high yields.